PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TIRTA MAHAKAM RESOURCES TBK SAMARINDA - Heriyanto dan Novi Susanti (Prodi Ilmu Administrasi Negara, 2020)
The study aims to determine the effect of work stress and work motivation onemployee performance. Specifically this study aims to find out how theinfluence of job stress on employee performance and know how well theinfluence of work motivation on employee performance, and to know theinfluence of work stress and work motivation on employee performance at PT.Tirta Mahakam Resources Tbk Samarinda. In this study the main problem iswhether there is influence of work stress and work motivation on employeeperformance at PT. Tirta Mahakam Resources Tbk Samarinda partially orsimultaneously.The method of analysis used in this research is descriptive analysis methodand quantitative analysis that is by multiple linear regression analysis. Thepopulation in this study is the number of permanent employees in theproduction of PT. Tirta Mahakam Resources Tbk Samarinda in 2017 as manyas 792 population. The sample in this research using simple random samplingby using slovin formula technique, so sample taken as many as 266 samples ofemployees remain part production PT. Tirta Mahakam Resources TbkSamarinda.The results showed that the value of F arithmetic = 143,844, using thesignificance limit of 0.05, then obtained the significance value is smaller than0.05 is 0.000, it means that simultaneously the variable work stress and workmotivation significantly influence employee performance. The coefficient ofdetermination (R2) is 0,522 or 52,2%, hence coefficient simultaneously inexplaining variation or change of dependent variable (Y) found the influenceof free variable 52,2%, while the rest is 47,8%. The result of hypothesis testing(H1) through the calculation results obtained t count value of 15,444 with thesignificance level of 0.000 results is smaller than 0.05, which means that thehypothesis in this study Ho rejected and Ha accepted. This test statisticallyproves that work stress has positive and dominant effect to employeeperformance. The result of hypothesis testing (H2) through the calculationresults obtained t count value of 3.215 with the significance of the result of 0.001 is smaller than 0.05, which means that the hypothesis in this study Horejected and Ha accepted. This test statistically proves that the motivation hasa positive effect on the performance of employees of PT. Tirta MahakamResources Tbk Samarinda.